PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI CLOUD ACCOUNTING JURNAL ID DENGAN TINGKAT PEMAHAMAN PEMANFAATAN TEKNOLOGI OLEH PENGGUNA SEBAGAI VARIABEL MODERASI TERHADAP KUALITAS LAPORAN KEUANGAN PADA CV JAYA PERKASA ABADI - Ricky, Ricky; Maisyarah, Renny; Purba, Rahima Br. (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The aim of this research is to determine the application of the cloud accounting information system, the level of understanding of the use of technology by users and the level of understanding of the use of technology by users which is able to moderate the influence of the application of the cloud accounting information system on CV Jaya Perkasa Abadi. The research method used is quantitative associative. In this research, the data analysis technique used is statistical analysis using SPSS software. The results of partial hypothesis testing of the implementation of the cloud accounting information system have a positive effect on the quality of financial reports at CV Jaya Perkasa Abadi. The level of understanding of the use of technology by users has a positive effect on the quality of financial reports at CV Jaya Perkasa Abadi. The level of understanding of the use of technology by users weakens the relationship between the application of cloud accounting information systems and the quality of financial reports at CV Jaya Perkasa Abadi. Simultaneously implementing the cloud accounting information system, the level of understanding of the use of technology by users simultaneously has a significant influence on the quality of financial reports at CV Jaya Perkasa Abadi.